Effect of Learning Experience on the Topic of Aquatic Animals Feed Processing for First-Year High Vocational Certificate in Aquaculture in Surat Thani College of Agriculture and Technology - เกตุแก้ว นิตยา (Journal of Vocational Education in Agriculture, 2020)
The purposes of this research were: (1) to create aquatic feed production process learning experience table (2) to study the efficacy of the learning experiences; and (3) to compare the group scores before and after the larning experience. Learning about the aquatic feed production process, the population was a group of 9 first year students enrolled for High Vocational Certificate in Aquaculture in Surat Thani College of Agriculture and Technology. The experimental plan was a pre-test and post-test single group. The data were analyzed by statistics (mean, standard deviation and t-test). The results of the study showed that after constructing the table for aquatic feed production process learning experience and then used it in the teaching and learning process, the students were able to change behavior according to the specified teaching objectives. The students were able to expertly practice the production of aquatic animal feeds by themselves in a timely manner. The students scores after learning were higher than the scores before learning.